2010
DOI: 10.2903/j.efsa.2010.1679
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re‐evaluation of curcumin (E 100) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re-evaluating the safety of curcumin (E 100). Curcumin has been previously evaluated by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) and the EU Scientific Committee on Food (SCF). In 2004 JECFA allocated an ADI of 0-3 mg/kg bw/day. The Panel was not provided with a newly submitted dossier and based its evaluation on previous evaluations, additional literature that became available since then and the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Numerous clinical trials have shown good tolerability, safety, and efficacy of curcumin in the treatment of multiple chronic diseases-including cardiovascular diseases, diabetes, neurodegeneration, arthritis, and cancer-at doses up to 6-12 g/day [10,11,13]. In light of this, the United States Food and Drug Administration (FDA) has "Generally Recognized As Safe" (GRAS) curcumin as an ingredient in various food categories (0.5-100 mg/100 g) [29]; and the European Food Safety Authority (EFSA) Panel on Food Additives and Nutrient Sources added to Food (ANS), defined the Allowable Daily Intake (ADI) value of 0-3 mg/kg bw/day of curcumin as a food additive [30]. However, despite its potential therapeutic benefits, curcumin is poorly bioavailable due to its rapid metabolism, and the small portion of substance that is absorbed is extensively bio-transformed into its water-soluble metabolites, glucuronides, and sulfates [10].…”
Section: Curcumin: Functions Bioavailability and Deliverymentioning
confidence: 99%
“…Numerous clinical trials have shown good tolerability, safety, and efficacy of curcumin in the treatment of multiple chronic diseases-including cardiovascular diseases, diabetes, neurodegeneration, arthritis, and cancer-at doses up to 6-12 g/day [10,11,13]. In light of this, the United States Food and Drug Administration (FDA) has "Generally Recognized As Safe" (GRAS) curcumin as an ingredient in various food categories (0.5-100 mg/100 g) [29]; and the European Food Safety Authority (EFSA) Panel on Food Additives and Nutrient Sources added to Food (ANS), defined the Allowable Daily Intake (ADI) value of 0-3 mg/kg bw/day of curcumin as a food additive [30]. However, despite its potential therapeutic benefits, curcumin is poorly bioavailable due to its rapid metabolism, and the small portion of substance that is absorbed is extensively bio-transformed into its water-soluble metabolites, glucuronides, and sulfates [10].…”
Section: Curcumin: Functions Bioavailability and Deliverymentioning
confidence: 99%
“…E100 (curcumin) is authorized with MPL but may be used quantum satis in a number of food categories. EFSA concluded that at the maximum levels of use, intake estimates for adults for E100 were below the ADI, but not for children (EFSA, 2010b). Rosemary extract (E392) was also not included in the exposure assessment since there is no numerical ADI, however E392 is not classified as "ADI not specified" either.…”
Section: Market Surveymentioning
confidence: 99%
“…The Joint FAO/WHO Expert Committee on Food Additives (JECFA) assessed the food additive curcumin (turmeric rhizome extract) in 2003 and established an acceptable daily intake (ADI) of 0-3 mg/kg body weight (bw) (WHO, 2004a,b). In 2010, the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) adopted a scientific opinion on the re-evaluation of the food additive colour curcumin (E 100) (turmeric rhizome extract) and concluded that the available data set supports the ADI allocated by JECFA based on the NOAEL of 250-320 mg/kg bw per day from the reproductive toxicity study in rats for a decreased body weight gain in the F2 generation observed at the highest dose level, and an uncertainty factor of 100 (EFSA ANS Panel, 2010). In 2014, the European Food Safety Authority (EFSA) took into account additional information on the use of curcumin (E 100) in foods and carried out a refined exposure assessment (EFSA, 2014).…”
Section: Additional Informationmentioning
confidence: 99%
“…No toxic effects were observed in a phase I study in 25 patients with high-risk cancerous conditions, receiving up to 8 g of curcumin (99.3% of purity) per day for 3 months for anticancer treatment (Cheng et al, 2001, EFSA ANS Panel, 2010. No side effects were reported in 18 patients with rheumatoid arthritis treated with daily doses of 1.2 g curcumin for 2 weeks (Deodhar et al, 1980 as referenced by EFSA ANS Panel, 2010).…”
Section: Human Clinical Studiesmentioning
confidence: 99%